On soliton solutions for perturbed Fokas-Lenells equation - Gomez, Cesar A. S.; Roshid, Harun-Or; İnç, Mustafa; Akinyemi, Lanre; Rezazadeh, Hadi (Springer, 2022)
In this work, a variety of optical soliton solutions are derived for a nonlinear generalized equation with variable coefficients. At first, a computational approach is used to obtain solutions for the proposed model for a particular case. After, a generalized approach is considered to obtain other type of solutions given in a more general form. From the model considered here, the classical perturbed Fokas-Lenells equation is obtained and new optical soliton solutions for this last case are presented. Finally, some conclusions are given.
Keywords: Fokas-Lenells equation; Variable coefficients; Exact solutions; Computational method